Morphology and location of thrombus and sludge in patients with non-valvular atrial fibrillation - Jing Cui; Shi-Jun Xia; Ri-Bo Tang; Liu He; Xue-Yuan Guo; Song-Nan Li; Nian Liu; Cai-Hua Sang; De-Yong Long; Xin Du; Jian-Zeng Dong; Chang-Sheng Ma (BMC Cardiovascular Disorders, 2024)
Abstract Background Stroke and thromboembolism in nonvalvular atrial fibrillation (NVAF) primarily arise from thrombi or sludge in the left atrial appendage (LAA). Comprehensive insight into the characteristics of these formations is essential for effective risk assessment and management. Methods We conducted a single-center retrospective observational of 176 consecutive NVAF patients with confirmed atrial/appendage thrombus or sludge determined by a pre-ablation transesophageal echocardiogram (TEE) from December 2017 to April 2019. We obtained clinical and echocardiographic characteristics, including left atrial appendage emptying velocity (LAAeV) and filling velocity (LAAfV). Data analysis focused on identifying the morphology and location of thrombus or sludge. Patients were divided into the solid thrombus and sludge groups, and the correlation between clinical and echocardiographic variables and thrombotic status was analyzed. Results Morphological classification: In total, thrombi were identified in 78 patients, including 71 (40.3%) mass and 7 (4.0%) lamellar, while sludge was noted in 98 (55.7%). Location classification: 92.3% (72/78) of patients had thrombus confined to the LAA; 3.8% (3/78) had both LA and LAA involvement; 2.7% (2/78) had LA, LAA and RAA extended into the RA, the remained 1.2%(1/78) was isolated to RAA. 98.0% (96/98) of patients had sludge confined to the LAA; the remaining 2.0% (2/98) were present in the atrial septal aneurysm, which protrusion of interatrial septum into the RA. The thrombus and sludge groups showed low LAAeV (19.43 ± 9.59 cm/s) or LAAfV (17.40 ± 10.09 cm/s). Only LA dimension ≥ 40 mm was independently associated with the thrombus state in the multivariable model. Conclusion This cohort study identified rare thrombus morphology and systematically summarized the classification of thrombus morphology. The distribution of thrombus and sludge outside limited to LAA was updated, including bilateral atrial and appendage involvement and rare atrial septal aneurysm sludge. LAAeV and LAAfV were of limited value in distinguishing solid thrombus from sludge. Clinical Trial Number ChiCTR-OCH-13,003,729.